Powojenne osiedlanie pogranicza ziem czeskich po drugiej wojnie światowej i jego nowy kszałt = The settlement in the Czech borderland after World War II and its specific character - Čapka, František (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The settlement of the borderland after World War II was the biggest internal migration of people in the history of the Czech land. The process (including the forced migration) covered more than five million people. From the point of view timing as well as organization the settlement was conducted simultaneously with the forced migration of the German population from Czechoslovakia, particularly from the Czech region, Moravia and the Czech Silesia.
Keywords: pogranicze czeskie; II wojna światowa (1939-1945); przesiedlenia ludności